Paolo Zermani - Nel Sant'Andrea - Zermani, Paolo (Firenze Architettura, 2018)
The entrusted theme, in proceeding to the architectural and liturgical adaptation through the construction of the new transept and presbytery, was that of designing a renewed geography for the Basilica of Sant'Andrea in Mantua, in which the space, which had been compromised through a series of temporary interventions from the 19th century to the present, could recover both recognisability and meaning.